MEDICAL STUDENTS’ EVALUATION OF AN ENGLISH FOR SPECIFIC PURPOSES COURSEBOOK: A CASE IN VIETNAM - Thao Thanh Le; Que Thi Nguyet Phan; Mai Xuan Le (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
The current study investigates students’ evaluation of the English for Specific Purposes (ESP) coursebook taught at a medical college in the Mekong Delta, Vietnam. After using it for a year, the users, including medical students and their teachers, have given some unofficial feedback on the book. This study provided insightful official information about how its student users perceive the coursebook they were adopting. Data on the evaluations of the ESP coursebook were gained from questionnaires administered to 166 students majoring in nursing and pharmacy in charge of ESP programs. Semi-structured interviews were employed with four students to get more specific apprehension. The results of this study indicated that students were satisfied with the ESP coursebook in terms of the covering of four skills, the presence of vocabulary and grammar, relevant content, understandable social and cultural context, suitability for mix-level students. In addition, participants perceived that communicative skills were not sufficiently presented, examples in grammar were not more interesting, the illustrations were not diverse and enough, and the cover was simple but not appealing. Suggestions regarding the pedagogical implications for the adoption and evaluation of the coursebook were discussed.